Sosialisasi Kesehatan Gangguan Psikosomatis Menggunakan Media X Banner pada Lansia di Yayasan Panti Jompo Budi Sosial Batam - Jannah, Indah Nur Jannah (Welfare : Jurnal Pengabdian Masyarakat, 2023)
Psychosomatic is a disease that involves the mind and body, where the mind influences the body until the disease appears or gets worse. The purpose of this study was to determine the level of knowledge in the elderly after being given education through the X banner media. In this study, researchers used a quantitative approach by filling out a pre-post test questionnaire. The data collection method in this study was through observation, filling out pre-post test questionnaires and documentation. The results showed that the provision of education through the X banner media had significant results after the pre-post test was carried out, increasing the knowledge of the elderly so as to help the elderly open their minds, be aware, and be able to solve their own problems, so that the elderly became more comfortable with their condition and did not interfere with their daily activities. -days.